KARAKTERISTIK BEADS ISOLAT KONSORSIUM BAKTERI TERMOFILIK PENGHASIL BIOLISTRIK - Irdawati; Dwi Fatiha, Fathma (Universitas Cokroaminoto Palopo, 2025)
Alginate matrix in the form of beads plays an important role in the process of immobilizing bacteria and maintaining their viability and stability in Microbial Fuel Cell (MFC) systems. The use of beads contributes to increasing the efficiency of electron transfer from bacteria to electrodes, thus supporting more optimal biolectricity production. This study aims to assess the characteristics of beads resulting from the immobilization of isolates of bioelectric-producing thermophilic bacterial consortium. The research method used was descriptive with visual observation of the color, shape, diameter, and number of bacterial colonies on the beads. Beads were synthesized from 5% sodium alginate solution mixed with six combinations of bacterial isolates (MS 9&12, MS 9&17, MS 9&18, MS 12&17, MS 12&18, and MS 17&18). The results showed that all beads had a round shape, yellowish white color, and diameter between 3.0 mm to 4.0 mm. The largest diameter was produced by the combination of MS 12&18 and MS 17&18 isolates, while the largest number of colonies was found in the combination of MS 12&17.